Custodes Invicem Custodiunt: Commitment through Competition - ANEY, Madhav S. (Institutional Knowledge at Singapore Management University, 2011)
How can specialists in violence, such as the military or the police, commit not to expropriate from producers? In this paper we propose competition between these agents as one of the mechanisms that can deter predation. In our model, even if specialists in violence could expropriate all output costlessly, it is attractive to protect producers from predators. This is because there is a marginal defensive advantage and consequently defense is an effective way to potentially eliminate other specialists in violence, reducing competition and leading to higher future payoffs. Hence, producers can offer transfers to specialists in violence that make defense a dominant strategy, resulting in an equilibrium without predation. We therefore show that internal competition among specialists in violence is enough to keep predatory behaviour at bay and sustain economic incentives even in the absence of threats external to themselves. Our answer to the question of “who guards the guards” is that “the guards guard each other” (custodes invicem custodiunt). We test the model using a panel of countries and find that the competition effect we highlight is consistent with the data for countries at low levels of development.